Humoral and cellular immune response to tick-borne-encephalitis (TBE) vaccination depends on booster doses in patients with Juvenile Idiopathic Arthritis (JIA). Issue 40 (24th September 2021) - Prelog, M.; Almanzar, G.; Stern, R.; Robrade, K.; Holzer, M.T.; Winzig, C.; Kleines, M.; Stiasny, K.; Meyer, T.; Speth, F.; Haas, J.P.
Abstract: Juvenile Idiopathic Arthritis (JIA) patients living in areas with high prevalence of tick-borne-encephalitis-virus-(TBEV)-infection are recommended for administration of inactivated TBE-vaccination. However, there are serious concerns regarding protective vaccine-induced immune responses against TBEV in immunocompromised patients. The present study aimed to analyze the humoral and cellular immune response to TBE-vaccination in previously TBE-vaccinated JIA patients compared to healthy controls (HC) including investigation of IgG-anti-TBEV avidity, neutralization capacity, cellular reactivity by IFNgamma-ELISPOT and cytokine secretion assays. Similar IgG-anti-TBEV antibody concentrations, neutralization titers and cellular reactivity were found between JIA and HC. The number and the early timing of booster vaccinations after primary vaccination had the most prominent effect on neutralizing antibodies in JIA and on IgG-anti-TBEV concentrations in both JIA and HC. Administration of booster vaccinations made it more likely for JIA patients to have IgG-anti-TBEV concentrations ≥165 VIEU/ml and avidities >60%. TNF-alpha inhibitors had a positive and MTX administration a negative effect on humoral immune responses. In conclusion, irrespective of having JIA or not, vaccinated children showed similar humoral and cellular immunity against TBEV several years after primary TBE-vaccination. However, in JIA, booster vaccinations mounted a significantly higher humoral immune response than in JIA without boosters. Our results highlight the need for timely administration of boosters particularly in JIA. Although immunosuppressive treatment at vaccinations in diagnosed JIA had a negative effect mainly on TBEV-specific cellular immunity, most JIA patients mounted a favorable humoral immune response which was maintained over time. Thus, successful TBE-vaccination seems highly feasible in JIA patients with immunosuppressive regimens.